Government Regulation of Logistics: Theoretical and Practical Analysis - SYZDYKBAYEVA, Bakyt U.; RAIMBEKOV, Zhanarys S.; MUSSINA, Kamshat P.; BAIMBETOVA, Asel B.; DULATBEKOVA, Zhanar A. (Journal of Advanced Research in Law and Economics, 2019)
Despite the numerous studies available on state participation in regulating and managing logistics processes, the functions of the state remain undisclosed and not comprehensively described in a systematic way, which calls for an appropriate research. The purpose of the study is to justify the need for state regulation and support of logistics processes in Kazakhstan, to identify problems and instruments of state regulation in the realm of logistics processes. While preparing the article, general scientific methods and techniques were used, including methods of statistical research and comparative analysis, theoretical analysis, general theoretical research methods and techniques. The following results were obtained: the factors determining the state regulation of logistics activities were identified through application of system analysis, the functions of the state in the development and management of logistics were systematically described; The main directions of state regulation and state support of logistics are highlighted; the role of logistics in the policy of spatial development of territories is defined; Based on the review, problems and instruments of state regulation of logistics processes are identified. The forms of state participation in the management of logistics activities in Kazakhstan are systematically presented. Explicit recommendations are given on improving the functions of state bodies in developing and improving the efficiency of logistics, which is associated in the future with the development of a national logistics strategy in Kazakhstan. An important conclusion has been made that the role of the state is not only in regulating logistics processes, creating conditions and stimulating the development of logistics, but also in special importance of interaction between the state and entrepreneurship in the formation and implementation of a logistics strategy in the future - in the form of trade unions and associations of a specialized nature. This paper deepens the study regarding factors and functions of logistics regulation impact on the development of the country's economy. The implications of these recommendations may be useful to politicians in Kazakhstan and other developing countries